2014
DOI: 10.1017/s0140525x13001192
|View full text |Cite
|
Sign up to set email alerts
|

Differences in negativity bias underlie variations in political ideology

Abstract: Disputes between those holding differing political views are ubiquitous and deep-seated, and they often follow common, recognizable lines. The supporters of tradition and stability, sometimes referred to as conservatives, do battle with the supporters of innovation and reform, sometimes referred to as liberals. Understanding the correlates of those distinct political orientations is probably a prerequisite for managing political disputes, which are a source of social conflict that can lead to frustration and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
491
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 498 publications
(567 citation statements)
references
References 240 publications
36
491
8
2
Order By: Relevance
“…In both cases, levels of disgust are predictive of attitudes toward issues like gay marriage (Smith, Alford, Hibbing, Oxley & Hibbing 2012;Balzer & Jacobs 2011). Whereas reactions to disgust and other negative stimuli appear to be universally valenced (though differing in intensity; see Smith et al 2012;Hibbing, Smith & Alford 2014;Soroka & McAdams 2015), physiological responses to erotica are largely considered appetitive, though may be consciously evaluated both negatively and positively by different individuals. We posit the variance in these responses may help us understand preferences for four of the most contentious sex-related issues in modern American politics: abortion, gay marriage, sex education in schools, and premarital sex.…”
mentioning
confidence: 99%
“…In both cases, levels of disgust are predictive of attitudes toward issues like gay marriage (Smith, Alford, Hibbing, Oxley & Hibbing 2012;Balzer & Jacobs 2011). Whereas reactions to disgust and other negative stimuli appear to be universally valenced (though differing in intensity; see Smith et al 2012;Hibbing, Smith & Alford 2014;Soroka & McAdams 2015), physiological responses to erotica are largely considered appetitive, though may be consciously evaluated both negatively and positively by different individuals. We posit the variance in these responses may help us understand preferences for four of the most contentious sex-related issues in modern American politics: abortion, gay marriage, sex education in schools, and premarital sex.…”
mentioning
confidence: 99%
“…Two studies, one American and one English, have found that "conservatives" tend to have a larger right amygdala (Kanai et al, 2011;Schreiber et al, 2013). This has been seen as evidence of "fearfulness" on the political right (Hibbing et al, 2014). One could alternatively say that conservatives are less indifferent to distress in other people and that this political category is a proxy for an ethnic category-individuals of "old stock" northwest European descent.…”
Section: Affective Empathymentioning
confidence: 99%
“…Proponents of this view stress the "ancient and universal" reality of the liberalconservative division (Hibbing, Smith, & Alford 2014;see also Pinker 2002;Tuschman 2013), seeing the psychological origins of individuals' positions on this continuum as stemming from basic personality features such as openness and conscientiousness (Haidt 2012;Hibbing, Smith, & Alford 2013;Jost, Federico, & Napier 2009;Pinker 2002), conceptions of human nature (Pinker 2002;Tuschman 2013), moral foundations (Haidt 2012), negativity bias (Hibbing, Smith, & Alford 2014), and so on.…”
mentioning
confidence: 99%
“…An interesting question is why this debate, which ought to be empirically tractable-how much ideological coherence is there?-persists. One possible contribution to the disagreement has to do with the description of the primary division in public opinion as "economic" versus "social," with various researchers finding different levels of correlation between these groups of issues in public opinion (Carmines, Ensley, & Wagner 2012;Feldman & Johnston 2014;Hibbing, Smith, & Alford 2014;Hussey 2012;Klar 2014;Verhulst, Hatemi, & Eaves 2012). While the "economic" grouping is often justified, involving various issues relating to income redistribution and the provision of benefits for the needy, the "social" grouping might cast too wide a net, including issues relating to sexual lifestyles, religious fundamentalism, race, immigration, or criminal justice.…”
mentioning
confidence: 99%